PENGGUNAAN APLIKASI GOOGLE CLASSROOM UNTUK MENINGKATKAN HASIL DAN KEAKTIFAN BELAJAR BIOLOGI SISWA KELAS XI IPA.1 SMA NEGERI 1 KAPONGAN PADA MASA PADEMI COVID 19: SMA NEGERI 1 KAPONGAN - NUR LILA DIAMAYANTI (Dewan Pendidikan Bondowoso, 2022)
This research was conducted with the aim of increasing student learning outcomes and activeness in Biology subjects through the Google Classroom application for students of class XI IPA.1 SMA Negeri 1 Kapongan Situbondo during the Covid 19 pandemic. The type of research used by the author in this study is Classroom Action Research (CAR). Classroom action research can be defined as an action research carried out by the teacher as well as a researcher in the classroom or together with other people (collaboration) by designing, implementing and reflecting collaborative and participatory actions that aim to improve or improve the quality of the learning process in the classroom. class through a certain action in a cycle (Kunandar.2010). The subjects in this study were students of class XI IPA.1 SMA Negeri 1 Kapongan in the even semester of the 2020/2021 school year, totaling 25 students. This research was carried out at SMA Negeri 1 Kapongan which is located at Jalan Raya Banyuwangi, Landangan Village, Kapongan District, Situbondo Regency, Postal Code 68362 for 3 months, from February to April 2021. Data collection techniques carried out in this study were by: (1 ) Observation, (2) Interview, (3) Documentation. (4) Test. Based on the results of the research conducted, it can be concluded that there is a positive influence on online learning with the use of the Google Classroom application. So that it can affect the improvement of student learning outcomes. Then it was concluded that the use of the Google Classroom application could improve the biology learning outcomes of class XI IPA.1 students of SMA Negeri 1 Kapongan